Are universities supplying learning spaces that suit the technology available for teaching? - Glendinning, Janet (Department of Construction Economics and Management, 2016)
Purpose: The report investigates the manner in which spaces are currently designed and provided for learning in the context of higher education institutions, and whether these designs take into account the technology available for use in an educational environment. It therefore looks at the impact that these spaces have on the learning process and the related ability of planners to provide the necessary spaces for teaching, in relation to the context of a technologically enhanced teaching environment. Design/methodology/approach: A review of current literature is used to establish what types of spaces should be provided for teaching with technology in line with what is being done in universities abroad. Case studies of three universities will be used to gather data on the current trend in terms of the actual provision of space in universities. Interviews will be conducted with the participants of the case studies. Findings: Once the case studies are complete, data will be analysed to assess how well the selected universities are doing in terms of providing space that is suitable for the latest technology that is used in the field of education. Practical implications: In evaluating the spaces provided and the technology available, it will become apparent if the spaces provided are indeed relevant in terms of the technological world we live in. Originality/value: Most of the current research documented in the literature examines technology and how it influences learning space design. As such, this report compares these concepts with the reality of space provision in universities today and questions the relevance of Space Norms in the age of E-learning. Limitations: The report is limited to an investigation into Gauteng HEIs. Technology investigated is limited to types that are useful to teaching and is not an exhaustive range of technology available in the world. Spaces referred to are education spaces only. Institutions investigated are limited to face-to-face HEIs which are public institutions.